KARAKTERISTIK AKSESI KENCUR (Kaempferia galanga L.) BERDASARKAN KOMPONEN MINYAK ATSIRI PADA DUA LOKASI YANG BERBEDA: Characteristics of Galanga Accessions (Kaempferia galanga L.) Based on Essential Oil Components at Two Different Locations - Subaryanti; Triadiati; Yohana C. Sulistyaningsih; Dyah Iswantini Pradono (Jurnal Tumbuhan Obat Indonesia, 2023)
Rhizome with high productivity and content of bioactive ingredients is the hope to be achieved from the cultivation of galanga (Kaempferia galanga L.). Galanga is used traditionally as a medicine for stomach ulcers, colds, headaches, coughs, diarrhea, facilitating menstruation, skin diseases, and rheumatism. Production of secondary metabolites is influenced by environmental factors and the place of growth. This study aims to determine the effect of the growing environment from two different locations on the essential oil content and its constituent components from the rhizome of the galanga accessions. The samples observed were nine accessions of galanga harvested at 6 months which were planted in the Bogor, namely Darmaga (L1) and Cisarua (L2) with a altitudes of 214 m asl and 780 m asl with different agro-climatic conditions. The accessions tested included Purbalingga (PBG), Cilacap (CLP), Purworejo (PWJ), Karanganyar (KRA), Pacitan (PCT), Madiun (MAD), Galesia 1 (GAL 1), Galesia 2 (GAL 2), and Galesia 3 (GAL 3). GAL 1, GAL 2, and GAL 3 are high yielding varieties of galanga that have been released by the Minister of Agriculture of the Republic of Indonesia and used as comparisons based on their essential oil content. Observations were made on the levels of essential oils and their constituent compounds using GC-MS (Gas Chomatography-Mass Spectroscopy). Differences in growing places affect the content of essential oils and their constituent components from the rhizome of the galanga accession. Environmental factors that influence are sunlight and water availability. The highest essential oil content (3.78%) was obtained from the MAD accession planted in Cisarua (L2) and the highest EPMS compound (34.74%) was obtained from the PCT accession planted in Darmaga (L1). There were 73 compounds detected with four main components, namely delta-3-carene, pentadecane, ethyl cinnamate, and ethyl p-methoxy cinnamate (EPMS).